3D Printing and Characterization of Metamaterial Composite Structures for Absorbing and Shielding Electromagnetic Waves. Issue 1 (January 2021) - Yin, Lixian; Tian, Xiaoyong
Abstract: Electromagnetic (EM) absorbing and shielding materials possess critical position in defence field. However, traditional absorbing materials failed to achieve a wide absorption band because of the impedance mismatching between absorbing materials and air. And Traditional shielding materials, such as metals, failed to meet the increasing critical needs because of the large density, low corrosion resistance, difficulty in fabrication of complex structures. To solve these problems, a metamaterial composite structures with good performance on EM absorbing and shielding was proposed. The composite structure consists of a metamaterial absorber and a composite shielding structure. The metamaterial absorber is composed of graphene composite metamaterial whose impedance is gradually increased by tailoring the geometric parameter and graphene content. The shielding structure was prepared by continuous carbon fiber (CCF) reinforced composite. The composite structure was fabricated by multi-process 3D printing technology, with which different composites can be fabricated integrally without assembly. Experimental results showed that the absorption bandwidth of the composite structure was 32 GHz (4.5∼14.5 GHz, 17∼39 GHz), and the shielding effectiveness was larger than 63 dB. The excellent absorbing and shielding performance indicates that the composite holds great potentials in defense and that the design and fabrication method is useful for improving the defence survive ability in complex EM environment and fabricating EM functional structures cheaply, rapidly and facilely.